Hyunsoonleella sp. HU1-3 Increased the Biomass of Ulva fasciata - Wang, Han; Elyamine, Ali Mohamed; Liu, Yuchun; Liu, Wei; Chen, Qixuan; Xu, Yan; Peng, Tao; Hu, Zhong (Frontiers in Microbiology, 2022)
Green algae are photosynthetic organisms and are important in the coastal environment. Microbial communities associated with the surface of green algae have an effect on host’s health and nutrition. However, few species of epiphytic microbiota have been reported to play the role of growth promotion in the algal life cycle. In this study, 16S rDNA sequencing was used to characterize the changes of microbial composition colonizing the surface of Ulva fasciata during different growth stages. Some bacteria serving as growth-promotors were identified. The possible growth-promoting behavior of the strains was verified by co-culturing of the pure bacteria obtained from the surface of U. fasciata and their sterile host. Of the identified species, a new bacterial species, Hyunsoonleella sp. HU1-3 (belonging to the family Flavobacteriaceae) showed a significant promotion on the growth of U. fasciata. The findings also found many genes for the synthesis of growth hormone and cytokinin in the genome of Hyunsoonleella sp. HU1-3. This study for the first time identified the bacterium Hyunsoonleella sp. HU1-3 has growth-promoting effects on U. fasciata. Our findings not only provide insights into the establishment of microbiota harboring the surface of U. fasciata, but also indicates that Hyunsoonleella sp. HU1-3 is one of the important species promoting the growth of algae.